1982
DOI: 10.1111/j.1365-2621.1982.tb10148.x
|View full text |Cite
|
Sign up to set email alerts
|

Rehydration of Freeze‐Dried Cultures of Lactic Streptococci

Abstract: Cell suspensions (0.2 ml each) of three lactic streptococci were freeze-dried from distilled water. In order to determine the optimum conditions of rehydration the effect of different factors such as composition, temperature, and pH of rehydrating media on viability of the freezedried cells of the lactic streptococci has been studied. Rehydration of freeze-dried cells with 10% solution of dextrose, sucrose or reconstituted skim milk at pH 6.5 and 22°C can be recommended as optimum conditions for maximum recove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
13
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 13 publications
3
13
0
Order By: Relevance
“…As shown in Table 2, rehydration with GYM medium gave the maximum viability of O. oeni. Sucrose was a good rehydration medium for cells of lactic streptococci (Sinha et al 1982), with similar results reported by Record et al (1962) for Escherichia coli and other Gram-negative organisms. However, it was also noted that the cell viability of O. oeni decreased when freeze-dried O. oeni was rehydrated with 10% sugar solution, compared with phosphate buffer.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…As shown in Table 2, rehydration with GYM medium gave the maximum viability of O. oeni. Sucrose was a good rehydration medium for cells of lactic streptococci (Sinha et al 1982), with similar results reported by Record et al (1962) for Escherichia coli and other Gram-negative organisms. However, it was also noted that the cell viability of O. oeni decreased when freeze-dried O. oeni was rehydrated with 10% sugar solution, compared with phosphate buffer.…”
Section: Discussionsupporting
confidence: 64%
“…Bacterial cell survival during freeze-drying depends on many factors, including growth conditions (Palmfeldt and Hahn-Hägerdal 2000), protective medium (Font de Valdez et al 1983a), the initial cell concentration (Bozoglu et al 1987;Costa et al 2000), freezing temperature (Sanders et al 1999), and rehydration conditions (Sinha et al 1982;Font de Valdez et al 1985a, b). Protective agents play an important role in the conservation of viability.…”
Section: Introductionmentioning
confidence: 99%
“…The rehydrated samples were kept in a shaker (100 rpm) at 37°C for 30 min to release the cells from the microcapsules. Rehydration temperatures between 30 and 37°C were the best for post hydration viabilities (Sinha, Shukla, Lal, & Ranganathan, 1982). A minimum reconstitution period of 15 and 30 min at selected temperatures allowed the particles to dissolve and generate a homogeneous suspension (Muller, Stanton, Sybesma, Fitzgerald, & Ross, 2010).…”
Section: Enumeration Of the Free And Encapsulated Bacterial Cellsmentioning
confidence: 99%
“…An organism which survives the various steps of freezing, drying and storage may, nevertheless, lose its viability during rehydration (Sinha, Shukla, Lal, & Ranganathan, 1982). Therefore, rehydration is a critical step in the recovery of freeze-dried microorganisms, because cells that were subjected to sublethal injury may not be able to repair said damage if they are rehydrated under inappropriate conditions (Costa et al, 2000).…”
Section: Storage and Rehydrationmentioning
confidence: 99%